Legal controversies and ethical considerations concerning the property rights in the human body - Kamel, Maria (Riga Graduate School of Law, 2021)
When considering the rise of the biotech industry over the years, one might wonder if the procurement of the biological materials, that are necessary for the success of the industry, was done through ethical and safe measures, especially considering the stagnant position of many countries towards granting individuals ownership rights over their bodies. As such, this paper inspects and compares the current legal approaches that are used in certain common law and civil law jurisdictions to determine individuals’ rights over their bodies, and considers the bundle of rights concept and the law of equity as possible solutions to the ethical and equitable deficiencies observed in certain jurisdictions that employ the property law approach
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Property and real estate law; Human rights; Commercialization of biomaterials.; Body autonomy